Kekuatan Hukum Rekomendasi Badan Pengawas Pemilu Tentang Pemungutan Suara Ulang - Pattipeilohy, Grisko Vinno; Rugebregt, Revency Vania; Tita, Heillen Martha Yosephine (Faculty of Law, Universitas Pattimura, 2025)
Based on its authority, General Election Supervisory Body's (BAWASLU) has issued recommendations for implementing re-voting at several polling stations in the February 14 2024 elections in Ambon City. In reality, the General Election Commission (KPU) as the organizer of the General Election did not implement these recommendations. The legal problem is the legal strength of the BAWASLU recommendations so that they are not executed by KPU.The method used in this research is normative juridical, with a model approach, legislation and conceptual approach, which is supported by several empirical approaches as supporting legal materials needed.Based on its authority BAWASLU is obliged to issue recommendations regarding the Re-Voting; that the legal consequence of not implementing the BAWASLU Recommendation is that the Recommendation is disqualified, and the KPU is referred to the Honorary Council, or to obtain justice the matter is followed up with legal action in court